Supra-Word Units with a Turkic Component - Karimullina, Guzel Nurutdinovna; Sarekenova, Karlygash Kurmangalikyzy (International Journal of Criminology and Sociology, 2022)
The article presents an analysis of Turkic borrowings in the semantic aspect, particularly features of their functioning within set expressions. The materials for the study are academic dictionaries of the Russian literary language published from the 18th to the 20th centuries. These sources were chosen because the lexical variety of the language becomes, at a particular stage of its development, reflected in lexicographic sources, and most comprehensively – in explanatory dictionaries. This type of reference books is aimed at most fully comprise the everyday vocabulary of a literary language. Comparing the lexicographic sources of various periods, as well as a comparative analysis of the Turkic units contained in them, allows tracing the life of a borrowed word in a language and the stages of its assimilation in the receiving language, and identifying the features of functioning of the Turkic layer in the Russian vocabulary. Supra-word units with a Turkic component are also analyzed from the viewpoint of their lexicographic registration, i.e., in compliance with the parameter indicated in explanatory dictionaries. It was found that during their functioning in the Russian language, Turkisms broaden their sphere of usage and occur within phraseologisms, some of them being registered as early as in the 18th – 19th centuries.